Comparison of spatial classification rules with different conditional distributions of class label - Stabingis, Giedrius; Dučinskas, Kęstutis; Stabingienė, Lijana (Nonlinear Analysis: Modelling and Control, 2014)
In this paper spatial classification rules based on Bayes discriminant functions are considered. The novelty of this work is that the statistical supervised classification method is improved by extending the influence of spatial correlation between observation to be classified and training sample. Such methods are used for data containing spatially correlated noise. Method accuracy is tested experimentally on artificially corrupted images. This classification rule with distance based conditional distribution for class label shows advantage against other classification rule ignoring such influence and against other commonly used supervised classification methods.
Keywords: Bayes discriminant functions; supervised classification; spatial dependency